2021
DOI: 10.1007/s10869-021-09742-7
|View full text |Cite|
|
Sign up to set email alerts
|

Thinking About Thinking About Work: A Meta-Analysis of Off-Job Positive and Negative Work-Related Thoughts

Abstract: This article is based on data presented at the Southern Management Association 2020 Annual Meeting. We have no known conflict of interest to disclose.We are grateful to the researchers who responded to our requests for study information and Old Dominion University Libraries staff Beverly Barco, David Corona, Marelene Patac, and Robert Tench for fulfilling our interlibrary loan requests. We also thank Dr. James Smither and our two anonymous reviewers for their patience, encouragement, and invaluable feedback th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
66
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(77 citation statements)
references
References 190 publications
(124 reference statements)
3
66
1
Order By: Relevance
“…Moreover, fatigue should be related to higher levels of affective rumination. Recent empirical findings regarding reciprocal relationships between low psychological detachment and its expected outcomes demonstrate that higher strain levels may influence ruminative thoughts in the evening (Jimenez et al, 2022;Wendsche et al, 2021). Fatigue is a state common to human life and is often characterized by low mood, unfocused mental states, or unpleasant bodily states (Hockey, 2013).…”
Section: Prediction Of Affective Ruminationmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, fatigue should be related to higher levels of affective rumination. Recent empirical findings regarding reciprocal relationships between low psychological detachment and its expected outcomes demonstrate that higher strain levels may influence ruminative thoughts in the evening (Jimenez et al, 2022;Wendsche et al, 2021). Fatigue is a state common to human life and is often characterized by low mood, unfocused mental states, or unpleasant bodily states (Hockey, 2013).…”
Section: Prediction Of Affective Ruminationmentioning
confidence: 99%
“…Affective rumination, for example, has been linked to sleep impairments (Syrek et al, 2017), higher fatigue, and lower levels of vigor in the evening (Minnen et al, 2021) as well as health complaints and emotional exhaustion (Firoozabadi et al, 2018a) in cross-sectional, longitudinal, and diary studies. A recent meta-analysis further confirmed that affective rumination, which is categorized as "work-related thoughts and associated feelings, " is related to lower wellbeing and higher health complaints (Jimenez et al, 2022). Therefore, it is crucial to understand what leads to affective rumination to effectively prevent its occurrence.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…So far, metaanalytic findings with data from various occupations support the assumptions of the SDM. Psychological detachment from work negatively relates to work-related stressors and positively relates to indicators of wellbeing and physical and mental health [17][18][19][20], see also [21] for a summary). However, a recent review found that only a few studies investigated psychological detachment among teachers and called for more fine-grained study approaches in this profession [22].…”
Section: Introductionmentioning
confidence: 99%